The role of socially responsible human resource management in improving performance: An analysis of subjective well-being as a mediating variable - Alex Winarno; Anita Silvianita (Qubahan Academic Journal)
The study aims to reveal the dynamic interaction between institutions, organizations, and employees in implementing social responsibility HRM (SRHRM) in SOEs as an institutional pressure. This research utilizes the hypothetic deductive method. Data were collected through a survey of SOE employees, and 524 complete and outlier-free responses were collected. Data analysis used structural equation model techniques. SRHRM strengthens institutional mechanisms to ensure sustainability. Employee job satisfaction and engagement optimize SRHRM functions to support green and non-green performance. The integration of CSR into corporate HR governance affects organizational members' behavior and social structure. It has implications for the organization, society, and a sustainable global world while maintaining balance (triple bottom line). This study provides a comprehensive picture of companies' response mechanisms and proactive behavior in the face of pressure. The success of SRHRM lies in its ability to improve well-being (satisfaction and engagement), which develops based on felt obligation. The felt obligation is vital to employees' engagement with sustainability through green work outcomes.